Proud to be a Pathologist - Huang, MD, PhD, Qin (North American Journal of Medicine and Science, 2010)
My fascination on pathologic basis of disease dates back to the time when I was a medical student learning basal ganglia disease in China in the late 1970s. I never dreamed of practicing medicine in the United States of America until early 1992 when I entered my second year of postdoctoral training at Massachusetts General Hospital with my own NIH grant and met a physician from Columbia. He was a postdoctoral fellow in the lab next to ours. We became close friends. He strongly encouraged me to take the American medical board exam. I initially hesitated because I was not sure about my skills in the English language and I had been away from clinical practice for over 10 years. I explained my uneasiness to my friend and he offered his help. He let me use his board-review books. Thus, I tried the step one board exam and was surprised to have a decent score. I was determined to continue. After an intense review for a few more months after my regular working hours, I took and passed the step two.